Teachers’ Perception of Grammar: Isolated or Integrated? - Nurenzia Yannuar (Politeknik Negeri Padang, 2013)
Explicit teaching of grammar, despite being the most popular in Asia, is not the only key to the mastery of English. There are different successful approaches to the teaching of grammar, which might be interesting to explore. Aside from the famous traditional grammar teaching, there are others such as communicate approach to grammar teaching, isolated and integrated approach, as well combination of both isolated and integrated grammar teaching. The current study is interested in exploring the different views on grammar teaching as well as understanding how English teachers perceive grammar teaching itself.The result of the recent study has been able to give insights that grammar is still considered important by a group of people that has been trained in a specific course of grammar teaching (pedagogical grammar class). Recognizing the standpoint of a group of people who will be assigned the role of teachers is important, because it suggests how grammar will be taught in future language classrooms.